Polyamines (spermidine and putrescine) mitigate the adverse effects of manganese induced toxicity through improved antioxidant system and photosynthetic attributes in Brassica juncea. (December 2019) - Hussain, Anjuman; Nazir, Faroza; Fariduddin, Qazi
Abstract: Polyamines (PAs) are recognized as plant growth regulators that are involved in the stress management in various crops. In the current study, mitigative roles of spermidine (Spd) and putrescine (Put) were assessed in manganese (Mn) stressed Brassica juncea plants. Spd or Put (1.0 mM) were applied to the foliage of Brassica juncea at 35 days after sowing (DAS) grown in the presence of Mn (30 or 150 mg kg −1 soil). The higher level of Mn (150 mg kg −1 ) diminished photosynthetic attributes and growth, enhanced the production of reactive oxygen species (ROS) like hydrogen peroxide (H2 O2 ) and superoxide anion ( O 2 · − ) content, affected stomatal movement and increased the Mn concentration in roots and shoots of the plant at 45 DAS, whereas it enhanced the activities of various antioxidant enzymes and proline content in the foliage of Brassica juncea plants. On the other hand, treatment of PAs (Spd or Put) to Mn stressed as well as non-stressed plants resulted in a remarkable improvement in the stomatal behaviour, photosynthetic attributes, growth and biochemical traits, decreased the production of ROS (H2 O2 and O 2 · − ) and concentration of Mn in different parts of plant. It is concluded that out of the two polyamines (Spd or Put), Spd proved more efficient and enhanced growth, photosynthesis, and metabolic state of the plants which bestowed tolerance and helped the plants to cope efficiently under Mn stress. Highlights: Mitigative role of polyamines spermidine (Spd) and putrescine (Put) was established in manganese (Mn) stressed Brassica juncea plants. Mn (150 mg kg −1 ) diminished photosynthetic attributes and growth, enhanced the production of ROS like H2 O2 and O 2 · − content in plants. Spd or Put improved stomatal behavior, photosynthetic attributes, growth and biochemical traits in Mn stressed plants. Out of the two polyamines (Spd or Put), Spd proved more effective and decreased the accumulation of Mn in plants.